Spider diversity as an effort to mitigate insect pests in the Lingsar Vegetable Farming Area, West Lombok Regency - Ilhamdi, Moh. Liwa; Idrus, Agil Al; Santoso, Didik; Raksun, Ahmad; Wirajagat, Gde Cahyadi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Arthropods have many roles in an ecosystem, including as pest biocontrol agents. Spiders are part of a group of arthropods that carry out this function by being predators of insect pests. This research aims to analyze the diversity of spider types in the Lingsar District Vegetable Area, West Lombok Regency. Data was collected from January to April 2023 using a survey method with sweeping nets three times per week and pitfall traps every week on five routes (west, south, east, centre, and north). Identification of spider types is carried out referring to morphological characteristics, guided by the identification book. The samples obtained were analyzed using the Shannon-Weiner diversity index (H'). The research results showed that the spider species identified in the Lingsar Vegetable Area comprised 11 species belonging to 10 families. Zoropsis spinimana from the Zoropsidae family was found in all sampling lines and was the species with the highest number of individuals. The species with the lowest number of individuals found in only one route are Ctenus hibernalis (Ctenidae) and Cryphoeca silvicola (Cybaeidae). The diversity index ranges from 1.188-1.654 (medium category), with the highest diversity in the middle route. The list of names of spider types obtained has the potential to be used as a basis for developing biocontrol of agricultural pests using their natural enemies in the form of spiders on horticultural crops such as vegetables.